Determination of flow characteristics of stepped spillways - Dursun, O. Faruk; Ozturk, Mualla (Ice Publishing, 2016)
Stepped spillways have become a popular method in recent times. Stepped spillways are used commonly for both energy dissipation and aeration. In this study, the energy dissipation ratio and inception point location of stepped spillways with and without end sills were studied using computational fluid dynamic (CFD) methods. The analyses were carried out for two sill types and three s/h ratios. Flow characteristics and air inception points were determined for slope angles of 30 degrees, 40 degrees and 50 degrees. The results were compared and discussed with the other studies in the literature. The greatest energy dissipation ratio was obtained at the slope angle of 30 degrees for type 2A (i.e. stepped sill and s/h ratio of 0.30). Moreover, the greatest energy dissipation ratio was shown at the slope angle of 50 degrees for stepped spillways without end sills. It was found that the length of the non-aerated flow region was closely related to energy dissipation. Finally, the flow characteristics of the stepped spillways can be reliably determined by using CFD analysis.
Keywords: Hydraulics & hydrodynamics; hydrology & water resource; waterways & canals